1999
DOI: 10.1136/vr.145.17.497
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and cultivation of a spirochaete from bovine digital dermatitis

Abstract: An epizootic in farmed, market-size rainbow trout in Spain caused by a strain of Carnobacterium piscicola of unusual virulence. Diseases ofAquatic Organisms 17,87-99 UBELS, J. L. & EDELHAUSER, H. F. (1987) Effects of corneal epithelial abrasion on corneal transparency, aqueous humor composition, and lens of fish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 12 publications
1
46
0
Order By: Relevance
“…Recently, spirochaetes have been cultured successfully from cases of a related disease of cattle, bovine digital dermatitis, in the USA [11], Germany [12] and the UK [13]. The latter study used immunomagnetic separation to isolate a spirochaete from affected cattle [13]. The present study employed a similar approach in a case of SVOFR and described the morphological, biochemical and genotypic characteristics of the novel treponeme isolated.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, spirochaetes have been cultured successfully from cases of a related disease of cattle, bovine digital dermatitis, in the USA [11], Germany [12] and the UK [13]. The latter study used immunomagnetic separation to isolate a spirochaete from affected cattle [13]. The present study employed a similar approach in a case of SVOFR and described the morphological, biochemical and genotypic characteristics of the novel treponeme isolated.…”
Section: Introductionmentioning
confidence: 98%
“…The method used was as described previously for the isolation of a spirochaete from a case of bovine digital dermatitis [13]. Brie¯y, immunomagnetic beads (2.8 ìm diameter) covalently coated with polyclonal anti-rabbit IgG were obtained from Dynech (Billingshurst, Sussex).…”
Section: Immunomagnetic Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, only a limited number of treponemal species from DD lesions have been cultivated in vitro (11,14,19,36,37), and only one, Treponema brennaborense, has been formally classified (31). Consequently, culture-independent phylogenetic methods, such as comparative 16S rRNA gene sequence analysis and fluorescence in situ hybridization (FISH), are valuable tools in determining the diversity, phylogeny, prevalence, and spatial distribution of these unclassified DD spirochetes.…”
mentioning
confidence: 99%
“…However, despite extensive research, a specific infectious agent has not been identified, and it has been suggested that the disease may be a polymicrobial infection (Döpfer et al, 1997). The range of bacteria cultured from DD lesions includes Campylobacter sputorum (Shibahara et al, 2002), Porphyromonas levii, Fusobacterium necrophorum, Fusobacterium nucleatum, Prevotella oralis, Prevotella denticola, Prevotella bivia, Treponema brennaborense (Schrank et al, 1999) and as-yet unnamed treponemes (Demirkan et al, 1999;Stamm et al, 2002;Walker et al, 1995). By using culture-independent methods, such as immunocytochemistry and 16S rRNA gene sequence analysis, additional organisms were detected in lesions and were related to Bacteroides levii, Borrelia burgdorferi, Mycoplasma hyopharyngis and several Treponema species (Collighan & Woodward, 1997; Demirkan et al, 1998; Moter et al, 1998).…”
Section: Tierarztpraxis Ch-3186 Dü Dingen Switzerlandmentioning
confidence: 99%